A Case Report with Rare Complication: Bladder Explosion During Transurethral Resection of Prostate (TURP) - Sani, Muhammad Mahbubi; Surahmad, Fakhri; Santoso, Sonny Agus; Setiawan, Bekti (Brawijaya Journal of Urology, 2026)
Introduction. Transurethral Resection of the Prostate (TURP) remains the gold standard procedure for treating Benign Prostatic Hyperplasia (BPH). Although this procedure has proven to be effective, it carries the risk of complications, including rare complications such as bladder explosion. Bladder explosion can occur due to the accumulation of flammable gases, especially hydrogen during electrocauterization. Case. A 71-year-old man with a medical history of recurrent urinary retention underwent monopolar TURP. During the procedure, a burst sound was heard followed by a 7 cm bladder perforation on the anterior wall. Urgent bladder repair was performed with exploration and placement of cystotomy and retroperitoneal drain. The patient underwent postoperative recovery and the follow-up showed good results. Conclusion. Bladder explosion is a rare but serious complication of monopolar TURP that requires immediate surgical intervention. Increased awareness and implementation of preventive strategies can minimize the risk of this complication and reduce patient morbidity.